Development of a method for monitoring clubhead path and orientation through impact - Ellis, K. L.; Roberts, J. R.; Sanghera, J. (Procedia Engineering, 2010)
This study reports the development of a golf clubhead trajectory monitoring system which utilises PONTOS, a 3D motion analysis package from GOM. This paper demonstrates how this system can be used to monitor clubhead path and orientation and position throughout impact with future scope to simultaneously measure ball launch conditions. Six subjects performed 10 swings with a driver and a selection of these shots were analysed in detail. Face angle and dynamic loft were calculated as indicators of clubhead orientation and the effect of off-centre impacts on head rotation were quantified. When considering clubhead velocity, the flexibility of the system allowed velocities at different locations to be monitored. It was found that the velocity of the toe and heel differed by up to 5.7ms-1 at the moment of impact.